Evaluation of Human Resource Management on Job Placement of Officers - Habibie, Muhammad Farhan; Putri, Dian Utama Pratiwi; Nurdiansyah, Tubagus Erwin; Kurniawati, Meti (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Human resources (HR) is a very important factor that cannot even be separated from an institution.Employees who have work skills that are in accordance with their fields will improve their performance results, and vice versa if employees work not according to their fields, it will result in a decrease in performance.. The problem is gettingThe existence of inappropriate work placements and the lack of human resources in their services are the main factors for increased workload and less than optimal performance results. This study aims to determine the results of the Evaluation of Human Resource Management on Workplacement of Officers at UPT Puskesmas Pagelaran, Pringsewu Regency.This type of research is quantitative research. The design of this study uses a descriptive correlation with a cross sectional approach. This research was conducted at the UPT Puskesmas Pagelaran, Pringsewu Regency. This time it will be held on March 1-April 1 2023. The total population is 78 employees of the Pagelaran Health Center UPT. Total sample is 78 respondent. The sampling technique used non probability sampling with total sampling, the data collection instrument used a questionnaire and data analysis used the chi square test and the odds ratioThe results of the study obtained a p value of 0.000. This means that there is a Correlation between the Evaluation of Human Resource Management and the Work Placement of Officers at the UPT Puskesmas Pagelaran, Pringsewu Regency. Human resource management can influence how big the risk is in determining job placement by 6.125 times (OR= 6.125). It is hoped that the performance health center will further improve human resource management so that employee work placements are in accordance with their classification and can improve the quality of service to the community to be optimal.